Effect of Depth of Electroacupuncture on the IPSS of Patients with Benign Prostatic Hyperplasia. (12th December 2019) - Yuan, Hongwei; Wei, Na; Li, Yanfeng; Yu, Lifeng; Zhang, Yunshu; Ong, Wei Lin; Bai, Ni; Wang, Mengxi; Fu, Yuting; Liu, Yunxia
Abstract : This study aimed to evaluate the efficacy of electroacupuncture (EA) on Ciliao (BL 32) and Zhongliao (BL 33) acupoints at different depths for the treatment of benign prostatic hyperplasia (BPH) through a single-blind randomized controlled trial. All 120 patients diagnosed with BPH were randomly allocated to an experimental group (deep insertion group, DI group, n  = 60) and control group (shallow insertion group, SI group, n  = 60) 3 times a week for 4 weeks. The observed results included the International Prostate Symptom Score (IPSS), Quality of Life score (QOL), maximum urine flow rate (Qmax), and postvoid residual urine volume (PVR). After treatment, at both depths, the BPH symptoms of patients were improved by EA. There were significant differences between the IPSS, QOL, and the effective rate of the experimental group and the control group (P < 0.05 ). Although the observed PVR and Qmax were better than those before treatment, there was no statistical significance between two groups (P > 0.05 ). Thus, EA with deep insertion can effectively improve the patients' urinary symptoms and quality of life, and it will be suitable for clinical application.